Pinus sylvestris bark extract reduces the impact of Heligmosomoides bakeri infection on C57BL/6 but not on BALB/c mice (Mus musculus) - Berit Marie Blomstrand; Stig Milan Thamsborg; Håvard Steinshamn; Heidi Larsen Enemark; Inga Marie Aasen; Karl-Christian Mahnert; Kristin Marie Sørheim; Francesca Shepherd; Jos Houdijk; Spiridoula Athanasiadou (Parasitology)
Plant secondary metabolites (PSMs) may improve gastrointestinal health by exerting immunomodulatory, anti-inflammatory and/or antiparasitic effects. Bark extracts from coniferous tree species have previously been shown to reduce the burden of a range of parasite species in the gastrointestinal tract, with condensed tannins as the potential active compounds. In the present study, the impact of an acetone extract of pine bark (Pinus sylvestris) on the resistance, performance and tolerance of genetically diverse mice (Mus musculus) was assessed. Mice able to clear an infection quickly (fast responders, BALB/c) or slowly (slow responders, C57BL/6) were infected orally with 200 infective third-stage larvae (L3) of the parasitic nematode Heligmosomoides bakeri or remained uninfected (dosed with water only). Each infection group of mice was gavaged for 3 consecutive days from day 19 post-infection with either bark extract or dimethyl sulphoxide (5%) as vehicle control. Oral administration of pine bark extract did not have an impact on any of the measured parasitological parameter. It did, however, have a positive impact on the performance of infected, slow-responder mice, through an increase in body weight (BW) and carcase weight and reduced feed intake by BW ratio. Importantly, bark extract administration had a negative impact on the fast responders, by reducing their ability to mediate the impact of parasitism through reducing their performance and tolerance. The results indicate that the impact of PSMs on parasitized hosts is affected by host's genetic susceptibility, with susceptible hosts benefiting more from bark extract administration compared to resistant ones.